DETERMINANTS OF PERFORMANCE OF SMALL AND MEDIUM LIQUOR ENTERPRISES IN KENYA. A CASE OF TIGANIA EAST SUB-COUNTY, MERU COUNTY - Kanario, Hellen; Luketero, Dr. Stephen Wanyonyi (IJRDO - Journal of Applied Management Science, 2017)
The purpose of this study was to investigate determinants of performance of small and medium liquor enterprises in Meru County and specifically Tigania East Sub-County. On business location, the study unearthed that accessibility by customers influenced performance of business. The study also indicated that availability of Infrastructure, access to markets, social structures and that distance from the town Centre influenced performance of liquor business. On internal capacity, the study showed that size of the premises, social network, stock levels and customers/end user influence performance of liquor business. Aspects analyzes on owner demographics indicated that, age, team work, work experience and education level affect the performance their business greatly. The study also revealed that gender influence performance of liquor business. Lastly on competition the, existing competitors, new markets and illicit brews influence the performance of liquor business. The study discovered that new products and new entrants influence the performance liquor business.